2020
DOI: 10.1111/jch.13950
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hypertension in hospitalized children prescribed as‐needed antihypertensive medication

Abstract: Imperfect measurement conditions, transient blood pressure (BP) elevation due to pain or anxiety, and heavy clinical demands complicate hypertension (HTN) diagnosis in hospitalized children, and may prevent recognition of hypertensive episodes for children prescribed as‐needed (PRN) antihypertensive medication. The authors sought to describe the incidence and predictors of missed BP elevation among hospitalized children prescribed PRN antihypertensive medication at our hospital. BP data were retrospectively au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
0
0
2
Order By: Relevance
“…In patients in whom any of these situations was documented, drug initiation was indicated. In this study, two drugs were prescribed on average to each patient, which, in order of frequency, were diuretics and vasodilators in half the cases, followed by ACE inhibitors and calcium antagonists, which is different from that reported in the study by Kocher et al 28 , where the most common medication was nifedipine, followed by hydralazine.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In patients in whom any of these situations was documented, drug initiation was indicated. In this study, two drugs were prescribed on average to each patient, which, in order of frequency, were diuretics and vasodilators in half the cases, followed by ACE inhibitors and calcium antagonists, which is different from that reported in the study by Kocher et al 28 , where the most common medication was nifedipine, followed by hydralazine.…”
Section: Discussioncontrasting
confidence: 75%
“…In our study, patients were hospitalized, permanently surrounded by health personnel, with acute diseases or exacerbated chronic processes, pain, medical and surgical interventions, or psychological stress due to the disease. The study by Kocher et al 28 evaluated 616 records of blood pressure figures in children aged between 2 and 18 years in a hospital of North Carolina, USA, and found that, in 37% of these records, HT was appropriately identified, which is a frequency higher than ours but with a different study design, which may overestimate the results.…”
Section: Discussioncontrasting
confidence: 54%
“…En nuestro estudio los pacientes estaban hospitalizados, rodeados permanentemente por personal del área de la salud, con enfermedades agudas o procesos crónicos agudizados, dolor, intervenciones médicas y quirúrgicas o estrés psicológico por la enfermedad. El estudio de Kocher et al 28 evaluó 616 registros de cifras de presión arterial en niños entre 2 y 18 años en un hospital en Carolina del norte, EE.UU., encontrando que en el 37% de estos registros se reconoció de forma adecuada la HTA, frecuencia superior a la nuestra pero con un diseño del estudio diferente, lo que puede sobrestimar los resultados.…”
Section: Discussionunclassified
“…Los antihipertensivos se indican en HTA en estadio 1 en los casos en los que no hay respuesta con las medidas no farmacológicas, en HTA sintomática, en condiciones médicas coexistentes (diabetes mellitus), HTA secundaria, evidencia de daño a órgano blanco y en estadio 21,3,4 . En los pacientes en los cuales se documentó alguna de estas situaciones se indicó el inicio de fármacos, en este estudio en promedio se prescribieron dos medicamentos a cada paciente, que en orden de frecuencia fueron diuréticos y vasodilatadores en la mitad de los casos, seguidos por IECA y calcioantagonistas, diferente a lo reportado en el estudio de Kocher et al28 , donde el medicamento más frecuente fue el nifedipino, seguido de la hidralazina.…”
unclassified